Preparation method of high-activity iron tailings
By mixing and calcining the iron tailings with waste rock, and ball-milling the iron tailings with the slag, the problem of difficulty in improving the activity of the iron tailings in the existing technology has been solved, the preparation of highly active iron tailings has been achieved, and its use in building materials has been significantly improved. application performance.
Patent Information
- Application Number
- CN202411479691.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to effectively improve the activity of iron tailings, and simple high-temperature calcination cannot significantly improve its activity.
By mixed with iron tail sand with waste stone, the middle material is obtained, and then mixed with the slag to form a high -active iron tail sand. This method is mixed with high temperature burning and ball milling, which promotes the mines and transformation of minerals in iron tail sand, and increases its activity.
It significantly improves the activity of iron tail sand, enhances its gel characteristics and response capabilities, and improves its application performance in architectural materials.
Smart Images

Figure CN119349905A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and particularly relates to a method for preparing high-activity iron tailings. Background Art
[0003] Since tailings particles have good uniformity and inert characteristics, they are often used as building aggregates after classification; clay-containing tailings are calcined to increase their volcanic ash activity, and then used as auxiliary cementitious materials to replace cement clinker. Therefore, preparing tailings into filling cementitious materials to achieve "self-production and self-sale" of tailings is undoubtedly the best way to improve the utilization rate of tailings. Generally speaking, the finer the material, the higher its potential activity, and the greater its potential for preparation into cementitious materials. However, for ultrafine iron tailings, mechanical activation is already difficult to effectively improve its activity. Therefore, thermal activation is used to promote the decomposition of clay in iron tailings to form an amorphous phase, thereby improving its activity. Studies have shown that thermal activation can indeed improve the activity of iron tailings. When the calcination temperature is 700°C, the activity of iron tailings is the best. However, simply calcining iron tailings at high temperature still cannot effectively improve the activity of iron tailings itself. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing high-activity iron tailings. The method provided by the present invention can further improve the activity of the iron tailings.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing high-activity iron tailings, comprising the following steps:
[0007] Mix the iron tailings and waste rock, and calcine them to obtain intermediate material;
[0008] The intermediate material and slag are ball-milled and mixed to obtain the high-activity iron tailings.
[0009] Preferably, the iron tailings comprises the following components in percentage by mass: SiO2 75% to 77%, Al2O3 2% to 4%, CaO 3% to 4%, Fe2O3 11% to 12%, MgO 6% to 7%, Na2O 0.2% to 0.4%, K2O 0.4% to 0.6%, TiO2 0.05% to 0.15% and SO3 0.05% to 0.15%.
[0010] Preferably, the particle size of the iron tailings is 0.6-40 μm.
[0011] Preferably, the waste rock comprises the following components in percentage by mass: Al2O3 0.3% to 0.4%, CaO 62% to 63%, Fe2O3 0.1% to 0.3%, MgO 30% to 31%, Na2O 0 to 0.05% and K2O 0 to 0.05%.
[0012] Preferably, the particle size of the waste rock is 0.6 to 380 μm.
[0013] Preferably, the slag comprises the following components in percentage by mass: SiO2 30% to 31%, Al2O3 8% to 10%, CaO 38% to 40%, Fe2O3 0.4% to 0.5%, MgO 16% to 18%, Na2O 0.05% to 0.1%, K2O 0.4% to 0.6% and SO3 2% to 3%.
[0014] Preferably, the particle size of the slag is 0.6-200 μm.
[0015] Preferably, the mass ratio of the iron tailings to the waste rock is 7-8:2-3.
[0016] Preferably, the calcination temperature is 800-900° C., and the holding time is 1-3 hours.
[0017] Preferably, the mass ratio of the intermediate material to the slag is 0.5-1:0.5-1;
[0018] The ball milling mixing has a rotation speed of 150 to 250 rpm and a mixing time of 25 to 35 minutes.
[0019] The present invention provides a method for preparing high-activity iron tailings, comprising the following steps: mixing iron tailings and waste rock, calcining, and obtaining an intermediate material; ball-milling and mixing the intermediate material and slag to obtain the high-activity iron tailings. The present invention improves the activity of iron tailings by adopting a mixed calcination activation method. During the high-temperature calcination process, the minerals (such as iron oxides, silicates, etc.) in the iron tailings will undergo phase change and transformation to generate a more active mineral phase; when further mixed with slag materials, the active components (such as calcium oxides, silicates) in the slag and the minerals in the iron tailings are ball-milled to prepare dry materials, and in the subsequent application process, stirred and reacted at a fixed water-cement ratio to generate compounds with gelling properties; the calcium and silicon components in the slag will form calcium silicate compounds, which have strong gelling properties and can significantly improve the activity of the iron tailings; in addition, high-temperature calcination will also change the surface characteristics of the iron tailings. By increasing the specific surface area of the material and changing the chemical composition, the surface of the iron tailings can have more active sites, thereby improving its ability to react with other substances and further improving the activity of the iron tailings. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is the XRD diagram of iron tailings, waste rock and slag in the present invention;
[0021] Figure 2 It is a particle size analysis diagram of iron tailings, waste rock and slag in the present invention;
[0022] Figure 3 XRD diagrams of the hydration products of the samples in Test Example 3 at different ages. DETAILED DESCRIPTION
[0023] The present invention provides a method for preparing high-activity iron tailings, comprising the following steps:
[0024] Mix the iron tailings and waste rock, and calcine them to obtain intermediate material;
[0025] The intermediate material and slag are ball-milled and mixed to obtain the high-activity iron tailings.
[0026] The invention mixes iron tailings and waste rocks, performs calcination, and obtains intermediate materials.
[0027] In the present invention, the iron tailings preferably include the following components in percentage by mass: SiO2 75% to 77%, Al2O3 2% to 4%, CaO 3% to 4%, Fe2O3 11% to 12%, MgO 6% to 7%, Na2O 0.2% to 0.4%, K2O 0.4% to 0.6%, TiO2 0.05% to 0.15% and SO3 0.05% to 0.15%. In the present invention, the particle size of the iron tailings is preferably 0.6 to 40 μm.
[0028] In the present invention, the waste rock preferably includes the following components in percentage by mass: Al2O3 0.3% to 0.4%, CaO 62% to 63%, Fe2O3 0.1% to 0.3%, MgO 30% to 31%, Na2O 0 to 0.05% and K2O 0 to 0.05%. In the present invention, the particle size of the waste rock is preferably 0.6 to 380 μm.
[0029] In the present invention, the mass ratio of the iron tailings to the waste rock is preferably 7-8:2-3, specifically 7:3 or 8:2.
[0030] In the present invention, the calcination temperature is preferably 800-900°C, and the heating rate to the calcination temperature is preferably 10°C / min; the insulation time is preferably 1-3h, specifically 1h, 2h or 3h.
[0031] After obtaining the intermediate material, the present invention mixes the intermediate material and slag by ball milling to obtain the high-activity iron tailings.
[0032] In the present invention, the slag preferably includes the following components in percentage by mass: SiO2 30% to 31%, Al2O3 8% to 10%, CaO 38% to 40%, Fe2O3 0.4% to 0.5%, MgO 16% to 18%, Na2O 0.05% to 0.1%, K2O 0.4% to 0.6% and SO3 2% to 3%. In the present invention, the particle size of the slag is preferably 0.6 to 200 μm.
[0033] In the present invention, the XRD patterns of the iron tailings, waste rock and slag are as follows: Figure 1 The particle size analysis diagram of the iron tailings, waste rock and slag is shown in Figure 2 shown.
[0034] In the present invention, the mass ratio of the intermediate material to the slag is preferably 0.5-1:0.5-1, and more preferably 1:1. In the present invention, the rotation speed of the ball milling is 150-250rpm, specifically 150rpm, 180rpm, 200rpm or 250rpm; the time is preferably 25-35min, specifically 25min, 30min or 35min.
[0035] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.
[0036] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] In the following examples and comparative examples, the compositions of iron tailings, waste rock and slag are shown in Table 1;
[0038] Table 1 Composition of iron tailings, waste rock and slag / %
[0039]
[0040]
[0041] Examples and Comparative Examples
[0042] Preparation method: after iron tailings (particle size of 0.6-40 μm) and waste rock (particle size of 0.6-380 μm) are mixed according to a mass ratio, the temperature is increased to a calcination temperature at a heating rate of 10°C / min, and the temperature is kept to obtain an intermediate material;
[0043] The intermediate material and slag (with a particle size of 0.6 to 200 μm) are mixed according to a mass ratio and then ball-milled to obtain the high-activity iron tailings.
[0044] Table 2 Proportions and condition parameters of the embodiments and comparative examples
[0045]
[0046] Performance Testing
[0047] Test Example 1
[0048] The compressive strength of the high-activity iron tailings obtained in the embodiment and the comparative example was tested;
[0049] The test method is: after mixing high-activity iron tailings and water (water-cement ratio is 0.5) and stirring for 7 minutes, the slurry is injected into a cylindrical mold (diameter 5cm, height 5cm), and then cured to the target age under the curing environment (curing environment is 20±1℃, (RH)≥95%, and the curing days are 3d, 7d and 28d). The compressive strength of the test block is tested using a microcomputer-controlled electronic universal testing machine. A total of 3 test blocks are tested in each group of tests, and the average value is taken as the final compressive strength of the group;
[0050] The test results obtained are shown in Table 3;
[0051] Table 3 Compressive strength of high activity iron tailings obtained in Examples and Comparative Examples
[0052]
[0053]
[0054] It can be seen from Table 3 that the 3d strength of the sample increases with the increase of waste rock content, and the sample strength reaches a peak when the ratio of iron tailings to waste rock is 7:3. At the same time, with the increase of calcination temperature, the 3d strength of the sample decreases monotonically. When the calcination temperature increases from 800℃ to 900℃, the sample strength decreases slightly. With the increase of holding time, the 3d strength of the sample decreases. Through the range calculation, it can be seen that the order of factors affecting the range of sample 3d strength is as follows: RB>RA>RC, (factor A (iron tailings: waste rock), factor B (calcination temperature / ℃), factor C (holding time / h), the same below) In the early stage of hydration, the calcination temperature has the greatest influence on the sample strength, followed by the ratio of iron tailings to waste rock, and the holding time has the least influence. The optimal combination of sample 3d strength is the ratio of iron tailings to waste rock of 7:3, the calcination temperature of 800℃, and the holding time of 1h.
[0055] The 7d strength of the sample also increases with the increase of waste rock content. The sample strength is the largest when the ratio of iron tailings to waste rock is 7:3. As the calcination temperature increases, the 7d strength of the sample still decreases monotonically, and the strength is the highest at 800℃. As the holding time increases, the 7d strength of the sample decreases. The influence of various factors on the compressive strength of samples 3d and 7d is basically the same, but the 7d strength is significantly higher than the 3d strength, indicating that the strength of the sample increases significantly with the increase of curing time. Through the range calculation, it can be seen that the order of the factors affecting the range of the 7d strength of the sample is as follows: RB>RA>RC, the calcination temperature still has the greatest influence on the strength of the sample, the iron tailings and waste rock ratio has the second greatest influence, and the holding time has the least influence. The optimal combination of the 7d strength of the sample is consistent with that of 3d, that is, the ratio of iron tailings to waste rock is 7:3, the calcination temperature is 800℃, and the holding time is 1h.
[0056] The 28d strength of the sample also increases with the increase of waste rock content. As the calcination temperature increases, the 28d strength of the sample keeps a monotonous decrease. As the insulation time increases, the 28d strength of the sample decreases first and then increases. The sample strength is the highest when the insulation time is 1h. As the curing age increases, the sample strength increases further. Compared with 3d, the strength growth rate is more than 50%. It can be seen that the early strength of the sample is poor, but the later strength development is good. Through the range calculation, it can be seen that the order of the factors affecting the extreme difference of the strength of the sample 28d is as follows: RB>RA>RC. The influence of each factor on the strength of the sample remains unchanged, but due to the change in the strength growth rate, the optimal combination of the later strength is a ratio of iron tailings to waste rock of 7:3, a calcination temperature of 800℃, and a insulation time of 1h.
[0057] Test Example 2
[0058] Chemically bound water CBW content analysis:
[0059] After the compressive strength test in Test Example 1, the sample fragments were collected and soaked in isopropanol for 12 hours to terminate the sample hydration, and then the sample was dried at 40°C, ground with a mortar and passed through a 200-mesh sieve for thermogravimetric testing. A comprehensive thermal analyzer was used to heat at a heating rate of 10°C / min in a temperature range of 30 to 600°C to obtain a thermogravimetric curve, and the content of chemically bound water CBW in the sample was calculated according to the following formula;
[0060] The formula is:
[0061] Where CBW represents the chemically bound water content in the sample; M 50 and M 550 They represent the mass of the sample at 50℃ and 550℃ respectively.
[0062] The results obtained are shown in Table 4;
[0063] Table 4 Chemically bound water CBW content of high activity iron tailings obtained in Examples and Comparative Examples
[0064]
[0065] It can be seen from Table 4 that as the calcination temperature increases, the CBW content in the sample decreases monotonically, and as the holding time increases, the CBW content in the sample increases. As the curing time increases to 28d, the influence of calcination temperature and holding time on the CBW content in the sample decreases, which shows that as the curing time increases, the influence of calcination temperature and holding time on the CBW content in the sample is not significant. By comparing the R value of each factor, the primary and secondary relationships of each factor on the CBW content in the 3d and 28d samples are: RB>RA>RC, and the optimal combination is a ratio of iron tailings to waste rock of 7:3, a calcination temperature of 800℃, and a holding time of 1h.
[0066] Based on the comprehensive analysis of compressive strength and CBW content, as well as economic optimization and maximum utilization of iron tailings, the optimal combination of thermally activated iron tailings was determined to be A2B1C1, that is, the ratio of iron tailings to waste rock was 7:3, the calcination temperature was 800℃, and the insulation time was 1h.
[0067] Test Example 3
[0068] The hydration product obtained after curing the sample corresponding to Example 5 in Test Example 1 was analyzed, and the obtained XRD pattern is as follows: Figure 3 As shown;
[0069] from Figure 3 It can be seen that there is still a certain amount of inert quartz crystals in the iron tailings after calcination, resulting in a lower strength of the sample. Calcium hydroxide is formed by the addition of water to calcium oxide formed by the decomposition of calcined waste rock, and its continuous reaction is shown in the following reaction formula.
[0070] nCaMg(CO3)2→(n-1)MgO+MgCO3·nCaCO3+(n-1)CO2
[0071] CaCO3→CaO+CO2
[0072] CaO+H2O→Ca(OH)2
[0073] The main hydration products in the samples are CSH gel, calcite, ettringite and hydrotalcite. The crystallinity of ettringite and hydrotalcite gradually increases with the extension of curing time, indicating that the samples are continuously hydrated.
[0074] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing high-activity iron tailings, characterized in that: The following steps are involved: Mix the iron tailings and waste rock, and calcine them to obtain intermediate material; The intermediate material and slag are ball-milled and mixed to obtain the high-activity iron tailings.
2. The preparation method according to claim 1, characterized in that: The iron tailings include the following components in percentage by mass: SiO2 75% to 77%, Al2O3 2% to 4%, CaO 3% to 4%, Fe2O3 11% to 12%, MgO 6% to 7%, Na2O 0.2% to 0.4%, K2O 0.4% to 0.6%, TiO2 0.05% to 0.15% and SO3 0.05% to 0.15%.
3. The preparation method according to claim 1 or 2, characterized in that: The particle size of the iron tailings is 0.6-40 μm.
4. The preparation method according to claim 1, characterized in that: The waste rock comprises the following components in percentage by mass: Al2O3 0.3% to 0.4%, CaO 62% to 63%, Fe2O3 0.1% to 0.3%, MgO 30% to 31%, Na2O 0 to 0.05% and K2O 0 to 0.05%.
5. The preparation method according to claim 1 or 4, characterized in that: The particle size of the waste rock is 0.6 to 380 μm.
6. The preparation method according to claim 1, characterized in that: The slag comprises the following components in percentage by mass: SiO2 30%-31%, Al2O3 8%-10%, CaO 38%-40%, Fe2O3 0.4%-0.5%, MgO 16%-18%, Na2O 0.05%-0.1%, K2O 0.4%-0.6% and SO3 2%-3%.
7. The preparation method according to claim 1 or 6, characterized in that: The particle size of the slag is 0.6-200 μm.
8. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the iron tailings to the waste rock is 7-8:2-3.
9. The preparation method according to claim 1, characterized in that: The calcination temperature is 800-900° C., and the heat preservation time is 1-3 hours.
10. The preparation method according to claim 8, characterized in that: The mass ratio of the intermediate material to the slag is 0.5-1:0.5-1; The ball milling mixing has a rotation speed of 150 to 250 rpm and a mixing time of 25 to 35 minutes.
Citation Information
Cited By
Preparation method and application of alkali-activated iron tailing geopolymer adsorbent
CN121266527A
A method for preparing a filling material using a chlorite-containing tailing
CN122705214A